Different modes of regulation govern miRNA expression levels in Drosophila melanogaster - Lim, Mandy Yu Theng (Nanyang Technological University, 2019)
MiRNAs are a class of small non-coding RNAs that play important roles in post-transcriptional regulation of complementary target mRNAs. Loquacious (Loqs) is a dsRNA-binding protein that binds Dicer-1 to cleave pre-miRNAs into short duplexes. The maternally deposited Loqs protein in Drosophila could potentially complicate their study in zygotic mutants. Here, Loqs function was investigated in the complete absence of maternal and zygotic contribution by using a cell line established from loqs-null fly embryos. Genome-wide analysis of pre-miRNA structures showed that Loqs enhances processing of sub-optimal substrates with unstable base-pairing at the dicing site. Post-transcriptional mechanisms that regulate miRNA expression during fly embryogenesis are not well understood. Here, distinct half-lives of individual miRNAs and identity of terminal 5’ nucleotides were found to influence miRNA expression profiles. Overall, the results illustrate roles for dsRNA-binding proteins and miRNA stability in regulation of miRNA expression, demonstrating the complexity that underlies these processes.